Conflitos socioambientais e resíduos sólidos na Amazônia: aterro sanitário de Marituba-RMB/PA, quilombolas do Abacatal e o Movimento Fora Lixão - LUZ, Diana Dias da (Universidade Federal do Pará, 2022)
The destination of solid waste in most Brazilian cities is usually the Sanitary Landfills. The big problem around this theme is that many of these places do not strictly follow the mandatory environmental precepts recommended by the Law and thus cause several environmental and social damages to the communities that surround them. Therefore, this work presents as a general objective to understand the socio- environmental conflicts between the Urban Waste Processing and Treatment Center (CPTR) in Marituba of the company Guamá and the Quilombola Community of Abacatal. Having thus, the following specific objectives: to describe the political- administrative context of the implementation of the enterprise in Marituba; to analyze the main types of conflicts and to identify what were the resistance strategies of the community in the face of the problems suffered and as a product the elaboration of a Documentary to give visibility to the forms of resistance and the impacts caused. This enterprise, in turn, meets the demand of the Municipalities of Belém, Ananindeua and Marituba, located in the Metropolitan Region of Belém and is meeting some popular resistance by the organized social movement called: FORA LIXÃO! in the sense of ending its activities in the place where it is inserted. The concepts used in the context of the project are based on the current Environmental Legislation such as the National Solid Waste Policy and others and the theoretical contribution is anchored in Leff and Litlle. For the development of the work, qualitative research was used with methodological procedures such as: Bibliographic Research, Documentary Research, Participant Research and Field Research and others. In the results, Conflicts related to Social and Environmental Impacts generated by human and natural action were predominant.